Physicochemical properties and methane adsorption performance of activated carbon nanofibers with different types of metal oxides - Othman, F. E. C. (Korean Carbon Society, 2017)
In this study, composite PAN-based ACNFs embedded with MgO and MnO2 were prepared by the electrospinning method. The resultant pristine ACNFs, ACNF/MgO and ACNF/MnO2 were characterized in terms of their morphological changes, SSA, crystallinity and functional group with FESEM-EDX, the BET method, XRD and FTIR analysis, respectively. Results from this study showed that the SSA of the ACNF/MgO composite (1893 m2 g–1) is significantly higher than that of the pristine ACNFs and ACNF/MnO2 which is 478 and 430 m2 g–1, respectively. FTIR analysis showed peaks of 476 and 547 cm–1, indicating the presence of MgO and MnO2, respectively. The FESEM micrographs analysis showed a smooth but coarser structure in all the ACNFs. Meanwhile, the ACNF/MgO has the smallest fiber diameter (314.38±62.42 nm) compared to other ACNFs. The presence of MgO and MnO2 inside the ACNFs was also confirmed with EDX analysis as well as XRD. The adsorption capacities of each ACNF toward CH4 were tested with the volumetric adsorption method in which the ACNF/MgO exhibited the highest CH4 adsorption up to 2.39 mmol g–1. Meanwhile, all the ACNF samples followed the pseudo-second order kinetic model with a R2 up to 0.9996.